2020
DOI: 10.1186/s12917-020-02511-3
|View full text |Cite
|
Sign up to set email alerts
|

Alpha- and gammaherpesviruses in stranded striped dolphins (Stenella coeruleoalba) from Spain: first molecular detection of gammaherpesvirus infection in central nervous system of odontocetes

Abstract: Background Herpesvirus infections in cetaceans have always been attributed to the Alphaherpesvirinae and Gammaherpesvirinae subfamilies. To date, gammaherpesviruses have not been reported in the central nervous system of odontocetes. Case presentation A mass stranding of 14 striped dolphins ( Stenella coeruleoalba ) occurred in Cantabria (Spain) on 18th May 2019. Tissue samples were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 44 publications
2
16
1
Order By: Relevance
“…All the sequences obtained from this study belonged to the Alphaherpesvirinae subfamily in contrast to similar previous studies, in which both alpha and gammaherpesvirus were detected [27,34,35,40,44].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…All the sequences obtained from this study belonged to the Alphaherpesvirinae subfamily in contrast to similar previous studies, in which both alpha and gammaherpesvirus were detected [27,34,35,40,44].…”
Section: Discussioncontrasting
confidence: 99%
“…Herpesvirus sequences detected in BWs from our study should be then analyzed by species. Specifically, sequences from Cuvier's BWs are not novel sequences, displaying higher homologies (100-98.06%) with sequences from striped dolphins stranded in the Mediterranean Sea and central and northeast Atlantic coasts (the Canary Islands and Portugal) (MG437217, KY680657, KY680656, and KJ156331) [26,34,35] (Case 1) and with a sequence detected in other Cuvier's BW from the Mediterranean Sea (KP995682) (Cases 5 and 8). The sequence KP995682 can be considered novel since it shows the highest homology (83.98%) with the sequence detected in the brain of a striped dolphin stranded in the Mediterranean Sea in 2011 (KP995684), which in turn showed the highest homology with the sequence from Case 1 in our study (95.5%) and with the sequence KP995682 (83.98%).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, these animals are vulnerable to infectious diseases, some of which have implications for human public health and others of which may serve as indicators of environmental distress syndrome [1]. For example, several studies have reported herpesvirus (HV) infection in cetaceans , with prevalences of up to 62.5% [24] or 78.57% [21]. HV can establish latent infections [25,26], and stress and immunosuppression can then cause the virus to revert to an actively replicating state [27].…”
Section: Introductionmentioning
confidence: 99%